2010
DOI: 10.1073/pnas.1007422107
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of antigen-specific Treg vaccination in vivo

Abstract: The conversion of naive T cells into Treg can be achieved in vivo by delivery of antigen under subimmunogenic conditions. Here we have examined several drugs for their ability to enhance the conversion process in vivo and have found that the rapamycin analog everolimus potently enhances Treg conversion by interfering with T-cell costimulation, reducing cell division and thereby activation of DNA methyltransferase 1 as well as by reducing T-cell activation through the ATP-gated P2×7 receptor controlling Ca2 + i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
84
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 34 publications
(44 reference statements)
5
84
0
1
Order By: Relevance
“…Recombinant anti-DEC205 Abs fused to disease-relevant autoantigens have been developed and used successfully for tolerogenic protection in autoimmune disease models, including autoimmune diabetes (24,26) and EAE (14,18,25). In the present study, we show that administration of a single dose of recombinant anti-DEC205 Ab fused to the cartilage-derived immunodominant PG 70-84 efficiently ameliorates the severity of PG-induced arthritis.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Recombinant anti-DEC205 Abs fused to disease-relevant autoantigens have been developed and used successfully for tolerogenic protection in autoimmune disease models, including autoimmune diabetes (24,26) and EAE (14,18,25). In the present study, we show that administration of a single dose of recombinant anti-DEC205 Ab fused to the cartilage-derived immunodominant PG 70-84 efficiently ameliorates the severity of PG-induced arthritis.…”
Section: Discussionmentioning
confidence: 57%
“…DEC205 + DC-targeted dominant tolerance can be achieved by the Ag-specific enhancement of Foxp3 + regulatory T cell (Treg) activity (15-18, 24, 25), whereas recessive tolerance mechanisms include deletion and induction of anergy in pathogenic T cells (13,14,18,24). DEC205 + DC targeting has been shown to promote immune tolerance in the spontaneous NOD mouse model of autoimmune diabetes (24,26) and peptide-induced mouse models of experimental autoimmune encephalomyelitis (EAE) (14,18,25). Compared to peptide-induced autoimmune models such as EAE, PGIA is fundamentally different because disease is induced with whole protein, namely human cartilage-derived PG.…”
mentioning
confidence: 99%
“…Because administration of peptide Ag together with immunomodulatory reagents favors the induction of Ag-specific Tregs in vivo (32,53,54), we assume it should be desirable to include islet Ag peptide in the combination, and indeed such a combination promoted significant Ag-specific Treg expansion in the spleens and pancreatic lymph nodes (Fig. 2B, 2C).…”
Section: Discussionmentioning
confidence: 99%
“…The administration of IL-2/anti-IL-2 mAb (clone JES6-1) complexes in vivo has been shown to increase polyclonal Treg numbers in lymphoid organs (29). It has also been reported that the mammalian target of rapamycin inhibitor rapamycin can selectively inhibit proliferation of CD4 + effector T cells, enhance the expansion of Tregs (30,31), and maintain the stability of expanded Tregs (32,33). Therefore, we hypothesized that a combined treatment comprising an islet Ag (BDC2.5 cognate mimetope), IL-2/IL-2 mAb complexes, and rapamycin could act in synergy to expand Ag-specific Tregs in lymphoid organs.…”
mentioning
confidence: 99%
“…Recognition of agonist TCR ligand works as a key element for the initiation of Treg cell generation, a developmental program which can run intra- [93,94] or extrathymically [95][96][97][98][99][100]. Studies on extrathymic Treg cell generation in the peripheral adult immune system can have an important therapeutic potential.…”
Section: Extrathymic Differentiation Of Foxp3 Expressing Treg Cellsmentioning
confidence: 99%